Characterisation of grinding-relevant particle properties by inverting of a population balance model - Vogel, Lutz; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2002)
An approach for the quantitative characterisation of feed materials in impact grinding is presented. With the help of dimensional reasoning and a fracture mechanic model two material parameters can be derived which describe the breakage probability quantitatively. The influence of stress intensity (impact energy), stress number, initial particle size and material are separated clearly. The two derived material parameters can be determined by single particle impact experiments with narrow size fractions of the feed material. A single mastercurve for the selection function of five different polymers, limestone and glass describes the breakage behaviour for two decades of initial particle size. The procedure using narrow feed size fractions can be simplified by using feed material with a broad particle size distribution. Then the appropriate population balance has to be inverted in order to determine the particle properties. Both, the population balance and the inversion are presented and validated with experimental results.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.charac_6
Keywords: Breakage probability; Comminution; Mastercurve; Population balance